Efficacy of Formalin-killed Aeromonas hydrophila and Streptococcus sp. Vaccine in Red Tilapia - Prasad, S.; Areechon, N. (Our Nature, 2011)
Humoral response in red tilapia against formalin-killed Aeromonas hydrophila and Streptococ cus sp. vaccine administered by intraperitoneal injection was evaluated.The result indicated that A. hydrophila vaccine induced significantly differed (P<0.05) high mean peak antibody titers of 925.87±467.92 and 4983.47±1832.74 in both primary and secondary immune response, respectively. However specific antibody produced by red tilapia in response to administration of Streptococcus sp. vaccine revealed only weak secondary response of 101.33±45.38. In separate experiment, relative protection in red tilapia immunized with A. hydrophila and Streptococcus sp. vaccine was conducted. Immunization were done by direct immersion for 1 hr in vaccine suspension and then challenged 2 weeks after by immersing fingerlings for 6 hr with virulent A. hydrophila and Streptococcus sp. Percent cumulative mortality in vaccinated and unvaccinated groups was compared after 14 days of post challenge. Red tilapia immunized by A. hydrophila vaccine demonstrated a particularly high level of immunity (76.67%) compared with unvaccinated (43.33%). Streptococcus sp. vaccine greatly reduced the mortality in vaccinated (31.67%) compared with unvaccinated fish (55%) but these differences in mortality were insignificant (P>0.05). Results from this study indicated the importance of vaccine for increasing disease resistance against A. hydrophila and Streptococcus sp infection by stimulation of specific humoral immunity. However the most important factor must be the method of vaccine administration which should be effective and applicable to farm scale. DOI: 10.3126/on.v8i1.4333